Answer:
p = -
![(1)/(2)](https://img.qammunity.org/2021/formulas/physics/middle-school/ukxexrkoplrwscaxd96qbbkphc5fo6w2ur.png)
Explanation:
Given
p =
( factorise numerator and denominator )
x² - y² ← is a difference of squares and factors as (x - y)(x + y)
x² + xy ← factor out x from each term
= x(x + y) , thus
p =
← cancel (x + y) on numerator/ denominator
=
← substitute x = - 4, y = - 6
=
![(-4-(-6))/(-4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/btv71aihcdco98w2ef151gyaifps7szvyt.png)
=
![(-4+6)/(-4)](https://img.qammunity.org/2021/formulas/mathematics/high-school/ttv74xzoooej3m93p1eepvfj3yveyfx24g.png)
=
= -
![(1)/(2)](https://img.qammunity.org/2021/formulas/physics/middle-school/ukxexrkoplrwscaxd96qbbkphc5fo6w2ur.png)